2018
DOI: 10.1177/1060028018794860
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Medication Therapy Management Clinic on Glycosylated Hemoglobin, Blood Pressure, and Resource Utilization

Abstract: Patients with diabetes and receiving MTMC had greater A1C improvements, compared with controls, of 0.54% (P = 0.0067) at 6 months and 0.63% (P = 0.0160) at 12 months. At 6 months, SBP and DBP decreased in MTMC patients by 6.5 mm Hg (P = 0.0108) and 3.8 mm Hg (P = 0.0136) more than controls, respectively. At 12 months, those receiving MTMC services had SBP and DBP decreases, respectively, of 8.2 mm Hg (P = 0.0018) and 1.7 mm Hg (P = 0.2691) compared with controls. ED and hospital visits were not statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…This is consistent with studies conducted in Australia [ 32 ] and USA [ 33 ] that showed age and duration of diabetes are strongly associated with macro-vascular and microvascular events. Intervention brought about a reduction in HbA1c levels by about 0.92% from baseline and this is concordant with other numerous studies performed in pharmacist-managed ambulatory and community pharmacy diabetes care models [ 19 , 34 , 35 ]. The reduction is strongly attributed to the intervention, which targeted the optimization of medication therapy need, lifestyle modification and enhanced medication adherence through consultations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with studies conducted in Australia [ 32 ] and USA [ 33 ] that showed age and duration of diabetes are strongly associated with macro-vascular and microvascular events. Intervention brought about a reduction in HbA1c levels by about 0.92% from baseline and this is concordant with other numerous studies performed in pharmacist-managed ambulatory and community pharmacy diabetes care models [ 19 , 34 , 35 ]. The reduction is strongly attributed to the intervention, which targeted the optimization of medication therapy need, lifestyle modification and enhanced medication adherence through consultations.…”
Section: Discussionsupporting
confidence: 89%
“…Similar studies done elsewhere [ 39 , 40 ] reported a decrement following MTM service, with varied extent depending on guideline used for cut-off points, patients’ awareness to apply recommendations and other sociodemographic factors. Other clinical parameters including FBS and SBP were also reduced through the intervention as reported elsewhere [ 34 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 87%
“…The effectiveness of interventions may depend on the delivery methods and frequency of intervention to patients rather than the type of provider who delivered the intervention. While studies included in this review did not consistently report frequency of patient communication between study arms, among those that were effective, several reported that the interventions involved regular in‐person or phone communication with a care team member either on a scheduled or as‐needed basis 13,27,44 …”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous studies that have evaluated the benefits of pharmacist inclusion in T2DM management, there is consistent evidence that suggests that pharmacists can help improve clinical outcomes. [7][8][9][10] However, as pharmacists are becoming more integral to multidisciplinary health care teams in diabetes management, it is crucial not only to measure clinical outcomes but also to identify the particular activities that are driving change. This process is facilitated by understanding the perceptions of the patients who use the services.…”
Section: Discussionmentioning
confidence: 99%
“…and health-related quality of life. [7][8][9][10][11] These studies have included people from a broad demographic distribution, revealing that the improved outcomes extend to those most in need: underserved, minority populations with poorly controlled diabetes. 12,13 Whereas pharmacists working in multidisciplinary diabetes health care teams are helpful in improving outcomes, patient experiences of receiving care within these models are missing.…”
mentioning
confidence: 99%